Prognostic factors for the long term outcome after surgical celiac artery decompression in MALS - Anna Woestemeier; Alexander Semaan; Andreas Block; Jan Arensmeyer; Jonas Dohmen; Alexander Kania; Frauke Verrel; Martin Mücke; Jörg C. Kalff; Philipp Lingohr (Orphanet Journal of Rare Diseases, 2023)
Abstract Background The median arcuate ligament syndrome (MALS) is a rare disease caused by compression of the celiac artery (ORPHA: 293208). Surgical treatment of MALS aims to restore normal celiac blood flow by laparoscopic celiac artery decompression. However, surgical success rates vary widely between patients, therefore adequate selection of patients is essential to improve surgical outcome. Symptoms of MALS might also overlap with other chronic multi-system disorders such as mast cell activation syndrome (MCAS). So far, no clinical or radiological parameter was found to be predictive of the postoperative outcome. We, therefore, aim to study preclinical parameters in one of the largest MALS cohorts with the focus to identify patients that would benefit from surgical MAL release. Results By analyzing 20 MALS patients that underwent surgical celiac artery decompression, we found 60% of patients (12/20) had a postoperative relief of their symptoms and a simultaneous decrease of analgetic use. No demographic, radiologic or operative parameter was able to predict postoperative symptom relief. However, mast cell activation syndrome correlated significantly (p = 0.04) with persistent symptoms after the operation. Conclusions Overall, laparoscopic MAL release can provide immediate symptomatic relief. Despite the missing predictive value of demographic and imaging data, our data show a correlation between persistent symptoms and a co-existing mast cell activation syndrome. This suggests that MCAS symptoms might be interpreted as MALS symptoms in the presence of celiac artery stenosis and therefore surgical treatment should be evaluated carefully. Overall, the selection of patients who are most likely to respond to surgical MAL release may best be accomplished by an interdisciplinary team of gastroenterologists, radiologists and surgeons.